2020
DOI: 10.1093/mnras/staa1240
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical backflow in X-shaped radio galaxy PKS 2014−55

Abstract: We present MeerKAT 1.28 GHz total-intensity, polarization, and spectral-index images covering the giant (projected length l ≈ 1.57 Mpc) X-shaped radio source PKS 2014−55 with an unprecedented combination of brightness sensitivity and angular resolution. They show the clear ‘double boomerang’ morphology of hydrodynamical backflows from the straight main jets deflected by the large and oblique hot-gas halo of the host galaxy PGC 064440. The magnetic field orientation in PKS 2014−55 follows the flow lines from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 44 publications
4
69
0
Order By: Relevance
“…In a recent work presenting MeerKAT observations, Cotton et al (2020) have shown hydrodynamical backflow in action in a GRG in common with our sample (PKS 2014-55; see Bruni et al 2020), underlying how the host galaxy PA, and thus its interstellar medium, can originate the deflection when they are tilted with respect to the jet axis. From a simple bidimensional Gaussian fit of the optical emission from the Pan-STARRS image, we estimated a PA of 31 • ± 7 • for the host galaxy major axis, consistent with the one measured for the southern jet axis (∼34 • ): this alignment between jet and host galaxy major axis does not support the mentioned backflow scenario.…”
Section: J0318+684supporting
confidence: 73%
“…In a recent work presenting MeerKAT observations, Cotton et al (2020) have shown hydrodynamical backflow in action in a GRG in common with our sample (PKS 2014-55; see Bruni et al 2020), underlying how the host galaxy PA, and thus its interstellar medium, can originate the deflection when they are tilted with respect to the jet axis. From a simple bidimensional Gaussian fit of the optical emission from the Pan-STARRS image, we estimated a PA of 31 • ± 7 • for the host galaxy major axis, consistent with the one measured for the southern jet axis (∼34 • ): this alignment between jet and host galaxy major axis does not support the mentioned backflow scenario.…”
Section: J0318+684supporting
confidence: 73%
“…However, based on the currently accepted value of H 0 ∼ 70 km s −1 Mpc −1 , RGs larger than 0.7 Mpc are now also considered GRGs. In the compilation of GRGs by Kużmicz et al (2018), the EMU-PS area contains only a single GRG, namely PKS 2014−558, first mentioned as a GRG by Jones & McAdam (1992) and recently studied in detail by Cotton et al (2020).…”
Section: Giant Radio Galaxiesmentioning
confidence: 99%
“…This would suggest that the central black hole and its accretion disk underwent a significant precession recently, possibly during the current episode of radio-AGN activity, whereby the jet direction changed by ∼50 • in the plane of the sky. It is quite possible that such a precession may have been triggered by the ongoing galaxy interactions, and is the mechanism (of the many mechanisms proposed to explain the X-shape in radio galaxies; Cotton et al 2020;Hardcastle et al 2019) responsible for the observed X-shape of 3C 433.…”
Section: Hα In the Host Galaxy Of 3c 433mentioning
confidence: 99%